2013
DOI: 10.1111/j.2047-6310.2013.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity prevention and control in city recreation centres and family homes: the MOVE/me Muevo Project

Abstract: Background Interventions to prevent and control childhood obesity have shown mixed results in terms of short- and long-term changes. Objectives “MOVE/me Muevo” was a two-year family- and recreation center-based randomized controlled trial to promote healthy eating and physical activity among 5-8 year old children. It was hypothesized that children in the intervention group would demonstrate lower post-intervention BMI values and improve obesity-related behaviors compared to control group children. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 40 publications
(52 reference statements)
0
94
0
Order By: Relevance
“…11 Children in NIK had been recruited from neighborhoods, and those in MOVE were recruited around recreation centers. Both studies used targeted phone calls to households that had a child in the study age range.…”
Section: Methodsmentioning
confidence: 99%
“…11 Children in NIK had been recruited from neighborhoods, and those in MOVE were recruited around recreation centers. Both studies used targeted phone calls to households that had a child in the study age range.…”
Section: Methodsmentioning
confidence: 99%
“…The similar results came from a centre-based randomized controlled trial by Elder et al that reported lower consumption of fat and sugary beverage in the intervention group than in the control group. 5 Although, these data cannot tell us why these particular behaviours appeared to change, it is possible that reducing fat and sugary beverage consumption are relatively easy behaviours for families to implement compared with the more complex, multidimensional behaviour of physical activity. The review of 29 studies that was published by Oxford University Press showed that school-based interventions targeting both physical activity and diet combined were associated with significant improvement in BMI.…”
Section: Effectiveness Of Preventive Strategies In Reducing Overweighmentioning
confidence: 99%
“…4 In USA, the prevalence of overweight was 32% and obesity was 17%. 5 In India, the prevalence of overweight in children ranges from 9% to 27.5% and obesity ranges from 1% to 12.9%. 6 The increasing problem of overweight and obesity in preschool children is mainly due to modern lifestyle which promotes an imbalance between energy intake and energy expenditure, resulting in excessive fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The CA-CORD intervention is based on the study team's previous research, 29,[31][32][33][34][35][36] several systematic reviews, [8][9][10]21,[37][38][39][40][41] CA-CORD CAC input, and formative research. CA-CORD CAC members were identified during the grant-writing phase by responding to a request for participation in a community-wide approach to prevent and control childhood obesity.…”
Section: Development Of the Ca-cord Intervention Approachmentioning
confidence: 99%
“…In addition to changes in healthcare delivery, an adapted FWP 29,[32][33][34]36 was integrated into CDSDP's Programs Department and is being administered by a full-time CHW coordinator and implemented by six full-time CHWs. A key feature of the FWP is its delivery by CHWs within a healthcare system and the documentation of CHW support in the child's EHRs.…”
Section: Healthcare Interventionmentioning
confidence: 99%